Male Costume and Weapons as Attributes of the Presentation of Masculinity in the Armenian Traditional Culture - Gushchyan, Lusine; Neratova , Elizaveta (History and Culture, 2023)
The article discusses the ways of presenting the aesthetics of masculinity in two Armenian historical and cultural areas during the second half of the 19th - early 20th centuries. Based on the analysis of the corpus of objects preserved in one of the largest ethnographic museums in the world - the Russian Museum of Ethnography in St. Petersburg, the criteria for differences in the formation of two main types of costume complexes - western (Van men's costume) and eastern (“pan Caucasian” men's costume) are revealed. The main criterion for differences is singled out - the belt and the types of edged weapons associated with them. Daggers, sabers and checkers presented in the museum's collection are considered from the point of view of their inclusion in the Armenian culture. The article examines five items that were made by Armenian craftsmen, or existed in the Armenian environment in one capacity or another. A number of objects have epigraphic inscriptions, which make it possible to clarify their origin. The analysis of the material makes it possible to identify, first of all, the importance of the role of Armenian armorers in the Caucasus region and far beyond its borders, however, it is also important to determine the place of weapons in the presentation of the image of an Armenian man.